Unraveling the Metabolic Requirements of the Gut Commensal Bacteroides ovatus - Robert Fultz (Frontiers Media S.A., 2021)
Background: Bacteroidetes are the most common bacterial phylum in the mammalian intestine and the effects of several Bacteroides spp. on multiple facets of host physiology have been previously described. Of the Bacteroides spp., Bacteroides ovatus has recently garnered attention due to its beneficial effects in the context of intestinal inflammation. In this study, we aimed to examine model host intestinal physiological conditions and dietary modifications to characterize their effects on B. ovatus growth.Methods and Results: Using Biolog phenotypic microarrays, we evaluated 62 primary carbon sources and determined that B. ovatus ATCC 8384 can use the following carbohydrates as primary carbon sources: 10 disaccharides, 4 trisaccharides, 4 polysaccharides, 4 polymers, 3 L-linked sugars, 6 D-linked sugars, 5 amino-sugars, 6 alcohol sugars, and 15 organic acids. Proteomic profiling of B. ovatus bacteria revealed that a significant portion of the B. ovatus proteome contains proteins important for metabolism. Among the proteins, we found glycosyl hydrolase (GH) familes GH2, GH5, GH20, GH 43, GH88, GH92, and GH95. We also identified multiple proteins with antioxidant properties and reasoned that these proteins may support B. ovatus growth in the GI tract. Upon further testing, we showed that B. ovatus grew robustly in various pH, osmolarity, bile, ethanol, and H2O2 concentrations; indicating that B. ovatus is a well-adapted gut microbe.Conclusion: Taken together, we have demonstrated that key host and diet-derived changes in the intestinal environment influence B. ovatus growth. These data provide the framework for future work toward understanding how diet and lifestyle interventions may promote a beneficial environment for B. ovatus growth.